UMA PROPOSTA DE MODELO DE PROCESSO BASEADO EM UMA ABORDAGEM ÁGIL PARA CONSTRUÇÃO E GESTÃO DE CURSOS EaD NO CONTEXTO DA UNIVERSIDADE ABERTA DO BRASIL - BATISTA, Amélia Acácia de Miranda (2012)
Agile principles can be used appropriately in management of generic projects, including outside the object of study of computer science and allow a quick adaptation to new domains. In this work we propose a management process model of Distance Learning Courses (DLC) within the context of the Open University of Brazil (UAB). This process model aims to manage the flow of activities in the construction and management of a DLC. As a complement of the research work, a prototype tool resulting from process modeling was developed, whose application favored the validation of the proposed model performed by an illustrative example. The prototype was developed using Eclipse Modeling Framework and Java Server Pages, addition to JPA specification associated with the Hibernate framework for persistence of data. For these goals to be achieved, were performed activities such as UAB operating environment characterization, process tailoring and construction metamodels for each phase of the model (called the Agile-UAB). As academic contributions of this study, we detach: the generation of a domain specific language, modeling Kanban agile method adapted to the UAB and the construction of a project management tool DL. We still consider as the real benefit of this research the improvement of the control flow of activities involved in the construction of a distance learning course within the context of UAB.